Strategic Redirection through Litigation: Forgoing the anti-trafficking framework to address labour abuses experienced by migrant sex workers - Clancey, Alison; Mahon, Frances (Anti-Trafficking Review, 2020)
Response to the ATR debate proposition ‘It is worth undermining the anti-trafficking cause in order to more directly challenge the systems producing everyday abuses within the global economy.’